2021
DOI: 10.1111/cen.14470
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hypercalciuria and renal calcifications in chronic hypoparathyroidism: A cross‐sectional study

Abstract: Hypoparathyroidism (HypoPT) is a rare endocrine disease, which causes hypocalcaemia due to missing or inappropriately low plasma levels of parathyroid hormone (P-PTH). 1 In most instances, the disease emerges following neck surgery, which causes damage to the parathyroid glands. However, in approximately one-fourth of the patients, the disease is due to non-surgical causes, including genetic variants and autoimmunity. 2 Due to lack of PTH, the renal 1α-hydroxylase (CYP27B1) is not well-stimulated resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
(63 reference statements)
0
10
0
1
Order By: Relevance
“…The assessment of urinary calcium excretion identifies patients at risk of developing kidney stones and/or nephrocalcinosis and decline of renal function. Even if recent studies did not find a clear correlation between kidney stones and hypercalciuria (148), or between urinary biochemical parameters and kidney outcomes (146), patients with HypoPT should be considered at a high risk of developing nephrolithiasis, nephrocalcinosis (149), as well as chronic kidney disease (146), Table 4.…”
Section: Q9 Which Biochemical Parameters Should Be Monitored To Adjus...mentioning
confidence: 99%
“…The assessment of urinary calcium excretion identifies patients at risk of developing kidney stones and/or nephrocalcinosis and decline of renal function. Even if recent studies did not find a clear correlation between kidney stones and hypercalciuria (148), or between urinary biochemical parameters and kidney outcomes (146), patients with HypoPT should be considered at a high risk of developing nephrolithiasis, nephrocalcinosis (149), as well as chronic kidney disease (146), Table 4.…”
Section: Q9 Which Biochemical Parameters Should Be Monitored To Adjus...mentioning
confidence: 99%
“…Previous studies in patients with chronic hypoPT have linked elevated serum calcium concentration and increased calcium-phosphate product level with increased risk of CKD ( 11 , 27 , 28 ). A recent study showed that hypercalciuria and renal calcification did not fully explain the increased risk of renal insufficiency in patient with chronic hypoPT ( 29 ). The role of serum phosphate in the risk for urolithiasis or CKD is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate in the urine of patients with hypoparathyroidism is lower than that seen in the general population. According to recent studies, excessive calcium excretion might have a dominant role compared to phosphate metabolism, although uncertainty remains about this pathogenetic hypothesis [ 34 ].…”
Section: Phosphate In Hypoparathyroidismmentioning
confidence: 99%